Efficacy of the cyclolipopeptides fengycin and iturin A against postharvest pome fruit pathogens - Magwebu, Sinovuyo; Meitz-Hopkins, Julia C.; Pott, Robert W. M.; Lennox, Cheryl L. (Frontiers in Horticulture, 2023)
Botrytis cinerea (grey mould) and Penicillium expansum (blue mould), are major pome fruit postharvest pathogens and their control heavily relies on the use of one postharvest fungicide (fludioxonil). This study aimed to evaluate the efficacy of the cyclolipopeptides (CLPs) containing fengycin and iturin A in crude extract from Bacillus amyloliquefaciens metabolites as alternative biofungicide. The crude extract containing CLPs was applied with edible coating (zein as carrier) as a postharvest treatment against B. cinerea on ‘Packham’s Triumph’ pears and P. expansum on ‘Cripps Pink’ apples. Treatments were applied either as a dip in combination with a zein edible coating at pH 2.0 or pH 8.0, as a spray application with zein edible coating at pH 2.0 or pH 8.0. The efficacy of CLP applications was compared to the standard registered synthetic fungicide fludioxonil at a concentration of 299.0 mg.L-1. Treatments were applied to fruit either preventatively (spray) or curatively (dip or spray). The lowest mean blue mould incidence (68.6 %) was achieved when edible coating containing crude extract of B. amyloliquefaciens (CLP at pH 2.0) was applied as curative dip treatment. Botrytis cinerea infection was reduced by 92.6 % resulting in 5.7 % grey mould incidence in curative application of CLPs at pH 2.0. This result was not significantly different from the inhibitory action of the fungicide fludioxonil. These results indicate that CLPs show the potential to be an effective alternative bio-fungicide for the control of B. cinerea on pome fruit, in an optimised formulation and application.